Fire, herbivores and the management of temperate Eucalyptus savanna in Tasmania: Introducing the Beaufront fire – mammalian herbivore field experiment. (30th December 2021) - Bowman, David M. J. S.; French, Ben J.; Williamson, Grant J.; Prior, Lynda D.
Summary: The temperate Eucalyptus savannas in the Midlands of Tasmania are ancient ecosystems where fire and grazing are intrinsic ecological disturbances. The arrival of Aboriginal people into Tasmania some 40, 000 years ago altered natural fire regimes, and since the end of the last ice age, their skilful patch burning increased the grass cover and the abundance of large grazers in the Midlands savannas. This ancient socio‐ecological tradition abruptly ended following European invasion in the early 19th century, which resulted in the rapid establishment of pastoralism, causing profound adverse changes to the ecological integrity of the temperate savannas. These changes include widespread tree clearing, extinction of native biota, establishment of domestic and feral mammalian herbivores, the introduction of exotic plants, broadscale application of chemical fertilisers and more recently irrigation. The Midlands retains a small fraction of the original vegetation, which typically occurs in small fragments on private land. These have been colonised by non‐native plants and animals, and experience altered fire regimes. There is a growing awareness that to effectively manage temperate savanna fragments may require the intentional coupling of fire and herbivory. We describe the establishment of a field experiment designed to test four broad hypotheses: a) herbivore off‐take increases after fire; b) smaller burned areas experience more intense herbivory than larger ones; c) non‐native herbaceous plants are more tolerant of herbivory, whereas native herbaceous species are more tolerant of fire; and d) Eucalyptus seedlings are most likely to reach maturity in areas which are both burned and protected from herbivores. A novel aspect of the fire‐herbivore experiment was that the Tasmanian Aboriginal community were engaged with and were contracted to conduct the burning. The findings of this landscape ecology experiment will inform the management of remnant temperate Eucalyptus savannas.